PEIRCE’S VISUAL SEMIOTIC IN EMOTIONAL CORRELATION MESSAGE AT “I CHOOSE AQUA” TV ADS - Andreas James Darmawan; Made Arini Hanindharputri; Kadek Adi Putra Wijaya (UPT Pusat Penerbitan LP2MPP ISI Bali, 2022)
In Charles Sanders Peirce's theory, visual semiotics is the thinking behind how the representative could present a message with a suitable object for the audience as an interpreter. This research is conducted to learn visualization as an object; that could represent emotional correlation in one of AQUA's advertisements, titled